Effect of pyrolysis, impregnation, and calcination conditions on the physicochemical properties of TiO2/Biochar composites intended for photocatalytic applications (2023)
Biochars are outstanding materials obtained from the pyrolysis of biomass, possessing unique physicochemical properties that are attractive for many environmental applications, including photocatalysis. In this work, we have synthesized for the first time TiO2/Biochar composites using Aeroxide P25 TiO2 and biochars produced from the thermal treatment at low (or null) oxygen content of Colombian coconut shells. To explore and ultimately tune the final physicochemical properties of the TiO2/Biochars materials, a facile wet impregnation method was assessed, in which the following factors were evaluated: 1) Temperature and 2) %O2 in the pyrolysis of the biomass, 3) TiO2/Biochar ratio used in the impregnation and 4) Calcination temperature of the TiO2/Biochar composites. A comprehensive characterization of the novel composites was done, using techniques such as: XRD, XPS, BET, ATR-FTIR, diffuse reflectance, PL, SEM, and electrochemical analysis. The material synthesized with TPyrol = 350 ◦C, %O2 = 2.5, T/B = 0.8 and TCal of 800 ◦C presented notable properties such as low Eg, reduced recombination of e--h+ pairs, a high surface area, and a relatively high photogeneration of charges, and interestingly, it experienced phase transition from Anatase-Rutile to Anatase-Brookite. On the other hand, low TPyrol and high %O2 values conduct to hydrophilic functional groups on the TiO2/Biochar composites, whereas the use of higher TPyrol and TCal lead to a more hydrophobic character but promote the reduction of the recombination of photogenerated e--h+ pairs. As a result, this information is relevant for planning future applications of photocatalysis for degrading pollutants of different chemical nature.